Antioxidant and free radical scavenging activity of ironchelators - Adjimani, J.P.; Asare, P. (Elsevier B.V., 2015)
Inside the human body, reactive derivatives of oxygen, known as reactive oxygen species(ROS) such as the superoxide radical (O2•), hydroxyl radical (•OH) and hydrogen perox-ide (H2O2), are constantly generated. The ROS easily cause oxidative damage to variousbiomolecules such as proteins, lipids and DNA leading to various disease conditions. Ironchelators function as antioxidants by scavenging ROS and also reduce the amount of avail-able iron thereby decreasing the quantity of•OH generated by Fenton reactions. In thisstudy, the antioxidant activity of the iron chelators: caffeic acid (CA), 2,3-dihydroxybenzoicacid (DHBA), desferroxamine B (FOB) and benzohydroxamic acid (BHA) were determinedusing five different in vitro antioxidant assays. The antioxidant assays used were: ironbinding ability, reducing ability using the potassium ferricyanide reduction method, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, H2O2scavenging activityand•OH scavenging activity. The standard used for the iron binding ability was Na2EDTAwhereas vitamin C was used as a standard for the remaining assays. The iron chelatorsshowed a concentration dependent increase in their radical scavenging activities as wellas their reducing ability. At the concentration of 1 mM, FOB had the highest iron bindingability of 93.7% whereas DHBA had the lowest iron binding ability of 5.0% compared to thestandard Na2EDTA which had 94.8%. The iron chelators, with the exception of BHA, showedgood reducing ability than vitamin C. Caffeic acid showed significant DPPH, hydrogen per-oxide and hydroxyl radical scavenging activities of 84.7%, 99.8% and 14.5%, respectively. Allthe iron chelators were observed to show significant activities in all five antioxidant assays.
Research Article
Keywords: Caffeic acid; Reactive oxygen species; Antioxidant activity; Iron binding ability; Reducing ability; Radical scavenging activitya